Peningkatan Kompetensi Guru Pembimbing Olimpiade Sains Nasional di MGMP Biologi SMA/SMK Kota Sabang - Safrida Safrida; Fitrah Asmaul Husna; Ikhsan Ikhsan (Journal of Social Responsibility Projects by Higher Education Forum, 2022)
The city of Sabang has almost never won the Biology Science Olympiad (BSO) at the provincial level. This condition is caused by the quality of the Olympic coaches who are able to compete with other cities. To increase this competitiveness, the ICARE method was used to improve the abilities of Olympiad supervisors under the Biology MGMP SMA/SMK Sabang City. The training method is carried out using the modified ICARE method to increase the effectiveness of the training implementation. The impact of this training, 80% of the participants got their mentoring activity for the first time. All supervisors (100%) experienced an increase in knowledge related to the syllabus, 40% related to the question bank, and 40% related to Olympiads prediction questions. The use of ICARE is able to facilitate training carried out with different age-related training participants.